2010
DOI: 10.1007/s10260-010-0138-8
|View full text |Cite
|
Sign up to set email alerts
|

Group sequential tests under fractional Brownian motion in monitoring clinical trials

Abstract: Clinical trials, Fractional Brownian motion, Group sequential design, Hurst coefficient,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Aggregation may lead to test statistic being long-memory property as described in Beran (1994, pp. 14-16) and as discussed in Lai (2010), that fractional Brownian motion is a convenient model for long memory stochastic processes. It may capture part of the correlated increment structure and lead to better statistical inferences.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Aggregation may lead to test statistic being long-memory property as described in Beran (1994, pp. 14-16) and as discussed in Lai (2010), that fractional Brownian motion is a convenient model for long memory stochastic processes. It may capture part of the correlated increment structure and lead to better statistical inferences.…”
Section: Introductionmentioning
confidence: 97%
“…Overall, for the two types of reasons above, we should account for the dependence of the test statistics across time. FBM has been considered for statistical monitoring and recruitment of clinical trials (Lai et al, 2000;Lai, 2004;Lai et al, 2001;Lai, 2010;Zhang andLai, 2010, 2011). Results from Zhang and Lai (2010) showed that when H increases the boundary value, expected sample sizes and stopping times will decrease and power increases.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that this method has desired properties even for short series with between 20 and 100 observations. Lai (2010) and Zhang and Lai (2010) one-sided group sequential designs and its operating characteristics for various alpha spending functions and analysis times. Results demonstrated that when H increases the boundary values, expected sample sizes/stopping times decrease and power increases for one-sided testing.…”
Section: Introductionmentioning
confidence: 99%